EVALUATING THE IMPLEMENTATION OF QUALITY OF WORK LIFE PROGRAM AT BANK SULUTGO USING IMPORTANCE AND PERFORMANCE ANALYSIS (IPA) - Lumempow, Rani Anatasia; Worang, Frederik G.; Tumiwa, Johan R. (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2018)
Abstract: Quality of Work Life is all the original inputs which aim at improving the employee’s satisfaction and enhancing organizational effectiveness. The sample size of this research is 36 employees that currently working in Bank SulutGo Branch Office in Amurang. The result of this study shows that the indicators of each variables such as Adequate and Fair Compensation placed in Quadrant II, Safe and Healthy Working Conditions placed in Quadrant I, Immediate Opportunity of Use and Develop Human Capacities placed in Quadrant I and II, Future Opportunity for Continued Growth and Security placed in Quadrant III, Social Integration in the Work Organization placed in Quadrant II, Constitutionalism in the Work Organization placed in Quadrant I and III, Work and the Total Life Space placed in Quadrant III, the Social Relevance of Work Life placed in Quadrant II. So based on the findings in this research, there are some recommendation for Bank SulutGo Branch Office in Amurang.Keywords: quality of work life, human resource management, importance performance analysis.